Do human work interruptions bring positive affective responses?—Based on the mediation of coping potential and the moderation of polychronicity - Xiao Pan; Xiaokang Zhao; Huali Shen; Qilong Chen (Acta Psychologica, 2023)
This research aims to investigate the impact of human work interruptions on positive affective responses and their underlying mechanisms in the Chinese context. In the first stage, this study conducted face-to-face semi-structured interviews with 29 employees representing diverse industries. The grounded theory research method was used to extract the construct of human work interruption, identify its core attributes, and capture the naturally emerging storyline of “human work interruptions - coping potential - polychronicity - positive affective responses”. In the second stage, a theoretical model was constructed and validated using 362 questionnaires. The results indicate that in the Chinese context: (1) human work interruptions can trigger positive affective responses; (2) coping potential mediates the relationship between human work interruptions and positive affective responses; (3) when individuals have a higher level of polychronicity, the impact of human work interruptions on positive affective responses via coping potential is enhanced. The findings of this study effectively address the hypothesis of the “positive aspect” of work interruptions proposed by management scholars and contribute to the existing literature on work interruptions and positive affective responses. Moreover, this research provides practical and theoretical implications for managers and employees in managing and coping with human work interruptions.